FOESG: anonymous session key agreement protocol for fog assisted smart grid communication. (2nd March 2023) - Mishra, Dheerendra; Rana, Saurabh; Goyal, Chirag; Singh, Gagandeep
To present a secure and authorised communication among customers, smart meters, utilities and smart grid (SG) communication should adopt a cryptographic mechanism to ensure involved entities' authentication, message integrity and confidentiality. To address efficient ways of authentication and secure session establishment, we construct an anonymous session key agreement protocol for the smart grid environment. This construction also uses fog as a specialised middle layer technique to make communication efficient. The formal proof of security is demonstrated under the widely adopted random oracle model (ROM) along with performance evaluation. Moreover, simulation for security validation is performed under broadly-accepted 'automated validation of internet security protocols and applications', which indicates that the protocol is safe. Comparison with recent proposals demonstrates an advantage in efficiency. In a nutshell, the proposed protocol achieves desirable security goals and performance attributes.